2007
DOI: 10.1159/000102919
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a New Dysfunctional Voiding and Incontinence Scoring System in Predicting Treatment Effect in Children with Voiding Dysfunction

Abstract: Aim: To assess the role of the dysfunctional voiding and incontinence scoring system (DVAISS) in children with voiding dysfunction. Methods: Ninety-three children were divided into three groups: those who had wetting only (group 1), recurrent urinary tract infections (UTIs) and wetting (group 2) and vesicoureteral reflux together with wetting and UTIs (group 3). Individualized multiple treatments modalities were applied. The success criteria defined by the reduction in the rate of wetting described as complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In our study, we have noticed that a higher sensitivity for the translated DVISS SR was higher for lower scores (score of four vs. score of nine) compared to the previous study, where the proposed cut-off value was 8.5 with a sensitivity of 90% and a specificity of 90% [3]. Additionally, in another study, the cut-off value was proposed to be nine, with a sensitivity of 100% and a specificity of 79.4% [4]. However, our specificity did not differ between scores of four and nine, indicating the same level of power to predict those subjects without dysfunctional voiding.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our study, we have noticed that a higher sensitivity for the translated DVISS SR was higher for lower scores (score of four vs. score of nine) compared to the previous study, where the proposed cut-off value was 8.5 with a sensitivity of 90% and a specificity of 90% [3]. Additionally, in another study, the cut-off value was proposed to be nine, with a sensitivity of 100% and a specificity of 79.4% [4]. However, our specificity did not differ between scores of four and nine, indicating the same level of power to predict those subjects without dysfunctional voiding.…”
Section: Discussionmentioning
confidence: 91%
“…The DVISS questionnaire is composed of 13 questions concerning voiding dysfunction and incontinence and one question regarding quality of life (Supplementary Material Table S1). The score range varied between 0 and 35 [4]. The first and the third questions were graded: 0, 1, 3 and 5; the second question was graded: 1, 3 and 5; the fourth question was graded: 1 and 4; the fifth, the seventh, the tenth and the thirteenth questions were graded: 0 and 1; the sixth was graded: 0 and 4; the eight, the ninth, the eleventh and the twelfth were graded: 0 and 2; while the fourteenth question (quality of life) was graded 0, 1, 2 and 3.…”
Section: Methodsmentioning
confidence: 99%
“…In 2005, one of the first DVAISS for children was introduced by Akbal et al 13 In a prospective study, Tuygun et al reported its efficacy in monitoring and managing children with dysfunctional voiding and confirmed the relevance of the cutoff score (8.5) as suggested by the DVAISS. 16…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, one of the first DVAISS for children was introduced by Akbal et al 13 In a prospective study, Tuygun et al reported its efficacy in monitoring and managing children with dysfunctional voiding and confirmed the relevance of the cutoff score (8.5) as suggested by the DVAISS. 16 The DVAISS was selected in our clinic based on the good validation of the score with a large number of patients as well as the control group. Further, it was possible to assess the clinical course with the calculated score.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the female, a thorough inspection for vaginal wall prolapse should be always made, since they could account for obstructive symptoms, even in initial cases (Dancz & Ozel, 2011). For pediatric patients also several questionnaires have been developed to assess voiding dysfunction (Tuygun et al, 2007). The most accepted is represented by the standardized dysfunctional voiding symptom score (DVSS) (Farhat et al, 2000).…”
Section: History Taking Examination and Questionnairesmentioning
confidence: 99%